2011
DOI: 10.1590/s0103-84782011001000010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e influência de rizóbios isolados de alfafa na germinação e desenvolvimento inicial de plântulas de arroz

Abstract: Caracterização e influência de rizóbios isolados de alfafa na germinação e desenvolvimento inicial de plântulas de arrozCharacterization and influence of alfafa rhizobia on germination and early growth of rice seedling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
0
1
0
2
Order By: Relevance
“…: no significant differences importance for increasing the competitiveness of the plants under study, under field conditions. Other authors also observed stimuli in the initial establishment phase of plants inoculated with rhizobia (Vargas et al, 2009;Stroschein et al, 2011;Tan et al, 2014), which is important interaction on growth and early crop development.…”
Section: Discussionmentioning
confidence: 88%
“…: no significant differences importance for increasing the competitiveness of the plants under study, under field conditions. Other authors also observed stimuli in the initial establishment phase of plants inoculated with rhizobia (Vargas et al, 2009;Stroschein et al, 2011;Tan et al, 2014), which is important interaction on growth and early crop development.…”
Section: Discussionmentioning
confidence: 88%
“…At the last reading the control treatment was not in the same vegetative stage as the others due to its later initial development. According to Stroschein et al (2011), evaluating the characterization and influence of rhizobia isolated from alfalfa on the germination and initial development of rice seedlings, they found that all rice seeds inoculated with rhizobia showed an initial increase in the percentage of twinning compared to the control treatment, in addition to increasing the twinning speed index of the seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Por exemplo, sementes de Mimosa tenuiflora inoculadas com diferentes rizóbios pode apresentar aumento no IVG (índice de velocidade de germinação), no comprimento de raízes e na massa seca de plântulas (SANTOS et al, 2017). Em arroz, a inoculação de sementes com os rizóbios Sinorhizobium e Rhizobium elevou o IVG de plântulas (STROSCHEIN et al, 2011;SOUZA 2017).…”
Section: Fundamentação Teóricaunclassified